Dreaming of a Christmas cowboy - Harlen, Brenda (Montana mavericks. The real cowboys of Bronco Heights., 2021)
A sudden Christmastime snowstorm gives Susanna Henry the chance to share her feelings with her longtime crush, rancher Dean Abernathy - but will she take it?